Extracorporeal membrane oxygenation (ECMO)‐assisted intratracheal tumor resection and carina reconstruction: A safer and more effective technique for resection and reconstruction. Issue 5 (19th February 2019) - Qiu, Yang; Chen, Qiao; Wu, Wei; Zhang, Shixin; Tang, Meng; Chen, Ya; Zhang, Chao; Zhou, Ni; Jiang, Nan; Feng, Jianping; Xia, Mei; Wang, Haidong
Abstract : Carina resection and reconstruction is required when a tracheal tumor invades the tracheal carina. It is a relatively complicated surgical procedure that requires complex reconstruction to maintain airway continuity. The technical difficulty lies in minimizing the influence of anesthetic endotracheal intubation and maintaining good ventilation function during surgery by establishing appropriate ventilation channels, which are contradictory in many cases. Therefore, in order to achieve the optimal surgical outcome, we performed intratracheal tumor resection and carina reconstruction with the help of extracorporeal membrane oxygenation.